STABILIZATION OF SOIL RESISTANCE IN NEW INSTALLATION IN THE COASTAL SOIL IN NIGER DELTA - Tarilanyo Afa, John; Okafor, E.N.C. (European Scientific Journal, ESJ, 2014)
Earthing is an intrinsic part of the electricity system and one of the requirements is to provide a sufficient low impedance to facilitate satisfactory protection and operation under fault conditions. In the coastal area of Niger Delta where the soil resistance is low due to the salt content of the subsoil water and the nature of soil the wanted advantage results to nuisance tripping of the protective device. This situation is common with the residual current device (RCD). This experience last for a period of 3 months to 6 months after that becomes normal. A study was carried out to identify the reasons of the local problem. The soil resistivity test was carried out in 10 different locations on the different soil at a depth of 1.0 to 1.5 meters, which is an approximate electrode planting depth for domestic installations. From the tests and analysis it was concluded that the low soil resistivity contributes to the nuisance tripping of residual current devices. If other protective devices (fuses) are used the nuisance tripping effect is not felt.